Застосування методу усереднення до дослiдження стiйкостi диференцiально-рiзницевих рiвнянь - Клевчук, I.I. (Нелінійні коливання, 2011)
Второе приближение в методе усреднения применено к исследованию устойчивости системы слабосвязанных осцилляторов с запаздыванием. Получено достаточное условие устойчивости (неустойчивости) линейной системы дифференциально-разностных уравнений. We use the second approximation in the averaging method to study stability of a system of weakly coupled oscillators with time delay. A sufficient stability (instability) condition is obtained for a linear system of differential-difference equations.